Parental Involvement and Mothers' Employment on Children's Independence During Covid-19 Pandemics - Insani, Asri; Yufiarti; Yetti, Elindra (Program Studi Magister Pendidikan Anak Usia Dini, 2021)
The pandemic that occurred this year created conditions that changed the activities of parents and children, the role of parents working outside the home often led to a lack of parental involvement in child development, especially the development of independence. The conditions of the Covid-19 pandemic have caused parents and children to be in one place at the same time. This study aims to determine the effect of parental involvement and maternal employment status on the independence of children aged 7-8 years in the Covid-19 pandemic situation. This quantitative research uses a comparative causal ex-post facto design, with groups of working mothers and groups of non-working mothers. The sample of each group was 60 people who were randomly selected. The findings of the study with the calculation of the two-way ANOVA test obtained the value of Fo = 4.616> F table = 3.92 or with p-value = 0.034 <α = 0.05, indicating that there is an interaction between parental involvement and maternal employment status on children's independence, and Based on the results of hypothesis testing, there is no effect of parental involvement and mother's work status on the independence of the child even though there are differences in the average results of children's independence. Keywords: Children's Independence, Parental Involvement and Mothers' Employment References: Areepattamannil, S., & Santos, I. M. (2019). Adolescent students’ perceived information and communication technology (ICT) competence and autonomy: Examining links to dispositions toward science in 42 countries. Computers in Human Behavior. https://doi.org/10.1016/j.chb.2019.04.005 Benner, A. D., Boyle, A. E., & Sadler, S. (2016). Parental Involvement and Adolescents’ Educational Success: The Roles of Prior Achievement and Socioeconomic Status. Journal of Youth and Adolescence, 45(6), 1053–1064. https://doi.org/10.1007/s10964-016-0431-4 Chusniatun, Kuswardhani, & Suwandi, J. (2014). Peran ganda pengembangan karier guru-guru perempuan. Jurnal Pendidikan Ilmu Sosial, 24(2), 53–66. Cohen, J. (1994). The earth is round (p < .05). (Vol. 49). American Psychologist,. DeLuca, C., Pyle, A., Braund, H., & Faith, L. (2020). Leveraging assessment to promote kindergarten learners’ independence and self-regulation within play-based classrooms. Assessment in Education: Principles, Policy & Practice, 27(4), 394–415. https://doi.org/10.1080/0969594X.2020.1719033 Dong, C., Cao, S., & Li, H. (2020). Young children’s online learning during COVID-19 pandemic: Chinese parents’ beliefs and attitudes. Children and Youth Services Review. https://doi.org/10.1016/j.childyouth.2020.105440 Eisenberg, N., Valiente, C., Morris, A. S., Fabes, R. A., Cumberland, A., Reiser, M., Gershoff, E. T., Shepard, S. A., & Losoya, S. (2003). Longitudinal relations among parental emotional expressivity, children’s regulation, and quality of socioemotional functioning. Developmental Psychology, 39(1), 3–19. https://doi.org/10.1037/0012-1649.39.1.3 Gassman-Pines, A., Ananat, E. O., & Fitz-Henley, J. (2020). COVID-19 and parent-Child psychological well-being. Pediatrics, 146(4). https://doi.org/10.1542/peds.2019-3211 Grolnick, W. S., Benjet, C., Kurowski, C. O., & Apostoleris, N. H. (1997). Predictors of Parent Involvement in Children’s Schooling. 11. Gürbüztürk, O., & Şad, S. N. (2010). Turkish parental involvement scale: Validity and reliability studies. Procedia - Social and Behavioral Sciences, 2(2). https://doi.org/10.1016/j.sbspro.2010.03.049 Gusmaniarti, G., & Suweleh, W. (2019). Analisis Perilaku Home Service Orang Tua terhadap Perkembangan Kemandirian dan Tanggung Jawab Anak. Aulad : Journal on Early Childhood. https://doi.org/10.31004/aulad.v2i1.17 Hatzigianni, M., & Margetts, K. (2014). Parents’ beliefs and evaluations of young children’s computer use. Australasian Journal of Early Childhood. https://doi.org/10.1177/183693911403900415 Hornby, G., & Lafaele, R. (2011). Barriers to parental involvement in education: An explanatory model. Educational Review, 63(1), 37–52. https://doi.org/10.1080/00131911.2010.488049 Iftitah, S. L., & Anawaty, M. F. (2020). Peran Orang Tua Dalam Mendampingi Anak Di Rumah Selama Pandemi Covid-19. JCE (Journal of Childhood Education), 4(2), 71. https://doi.org/10.30736/jce.v4i2.256 Jeynes, W. H. (2005). Effects of Parental Involvement and Family Structure on the Academic Achievement of Adolescents. Marriage & Family Review, 37(3), 99–116. https://doi.org/10.1300/J002v37n03_06 Kadir. (2017). Statistika Terapan. PT Raja Grafindo Persada. Komala. (2015). Mengenal dan Mengembangkan Kemandirian Anak Usia Dini Melalui Pola Asuh Orang Tua dan Guru. Tunas Siliwangi, 1(1), 31–45. Kumpulainen, K., Sairanen, H., & Nordström, A. (2020). Young children’s digital literacy practices in the sociocultural contexts of their homes. Journal of Early Childhood Literacy, 20(3), 472–499. https://doi.org/10.1177/1468798420925116 Levitt, M. R., Grolnick, W. S., Caruso, A. J., & Lerner, R. E. (2020). Internally and Externally Controlling Parenting: Relations with Children’s Symptomatology and Adjustment. Journal of Child and Family Studies, 29(11), 3044–3058. https://doi.org/10.1007/s10826-020-01797-z Lie, A., & Prasasti, S. (2004). Menjadi Orang Tua Bijak 101 Cara Membina Kemandirian dan Tanggung Jawab Anak. PT. Alex Media. Livingstone, S., Mascheroni, G., Dreier, M., Chaudron, S., & Lagae, K. (2015). How parents of young children manage digital devices at home: The role of income, education and parental style. 26. Mikelić Preradović, N., Lešin, G., & Šagud, M. (2016). Investigating Parents’ Attitudes towards Digital Technology Use in Early Childhood: A Case Study from Croatia. Informatics in Education, 15(1), 127–146. https://doi.org/10.15388/infedu.2016.07 Moonik, P., Lestari, H. H., & Wilar, R. (2015). Faktor-Faktor Yang Mempengaruhi Keterlambatan Perkembangan Anak Taman Kanak-Kanak. E-CliniC, 3(1), 124–132. https://doi.org/10.35790/ecl.3.1.2015.6752 Ogg, J., & Anthony, C. J. (2020). Process and context: Longitudinal effects of the interactions between parental involvement, parental warmth, and SES on academic achievement. Journal of School Psychology. https://doi.org/10.1016/j.jsp.2019.11.004 Pek, L. S., & Mee, R. W. M. (2020). Parental Involvement On Child’s Education At Home During School Lockdown. Jhss (Journal Of Humanities And Social Studies). https://doi.org/10.33751/jhss.v4i2.2502 Porumbu, D., & Necşoi, D. V. (2013). Relationship between Parental Involvement/Attitude and Children’s School Achievements. Procedia - Social and Behavioral Sciences, 76, 706–710. https://doi.org/10.1016/j.sbspro.2013.04.191 Raeff, C. (2010). Independence and Interdependence in Children’s Developmental Experiences. Child Development Perspectives, 4(1), 31–36. https://doi.org/10.1111/j.1750-8606.2009.00113.x Rantina, M. (2015). Peningkatan Kemandirian Melalui Kegiatan Pembelajaran Practical Life. Jurnal Pendidikan Usia Dini, 9, 181–200. https://doi.org/DOI: https://doi.org/10.21009/JPUD.091 Rihatno, T., Yufiarti, Y., & Nuraini, S. (2017). Pengembangan Model Kemitraan Sekolah Dan Orangtua Pada Pendidikan Anak Usia Dini. JPUD - Jurnal Pendidikan Usia Dini. https://doi.org/10.21009/jpud.111.08 Rika Sa’diyah. (2017). Pentingnya Melatih Kemandirian Anak. Jurnal KORDINAT, 16, 31–46. Yulianti, K., Denessen, E., & Droop, M. (2019). Indonesian Parents’ Involvement in Their Children’s Education: A Study in Elementary Schools in Urban and Rural Java, Indonesia. In School Community Journal. Zhang, D., Zhao, J. L., Zhou, L., & Nunamaker, J. F. (2004). Can e-learning replace classroom learning? Communications of the ACM, 47(5), 75–79. https://doi.org/10.1145/986213.986216